Global Poverty and Inequality : A Review of the Evidence - Ferreira, Francisco H.G.; Ravallion, Martin (World Bank, Washington, DC, 2012)
Drawing on a compilation of data from household surveys representing 130 countries, many over a period of 25 years, this paper reviews the evidence on levels and recent trends in global poverty and income inequality. It documents the negative correlations between both poverty and inequality indices, on the one hand, and mean income per capita on the other. It points to the dominant role of Asia in accounting for the bulk of the world's poverty reduction since 1981. The evolution of global inequality in the last decades is also described, with special emphasis on the different trends of inequality within and between countries. The statistical relationships between growth, inequality and poverty are discussed, as is the correlation between inequality and the growth elasticity of poverty reduction. Some of the recent literature on the drivers of distributional change in developing countries is also reviewed.